Adaptive system for correcting optical aberrations of high-power lasers with dynamic determination of the reference wavefront. (July 2021) - Kotov, A V; Perevalov, S E; Starodubtsev, M V; Zemskov, R S; Alexandrov, A G; Galaktionov, I V; Kudryashov, A V; Samarkin, V V; Soloviev, A A
Abstract: We present the results of the aberration correction of laser radiation wavefront using a dynamic method for determining the reference wavefront. The method, which is based on the processing of synchronously obtained data on the near- and far-field zones, significantly improves the focusing quality with active wavefront correction, especially under conditions of dynamic aberrations. An increase in the Strehl number S from 0.7 to 0.86 is demonstrated when a beam 18 cm in diameter is focused by an F/2.5 parabolic mirror.